Appraisal and analysis on various web service composition approaches based on QoS factors - M. Rajeswari; G. Sambasivam; N. Balaji; M.S. Saleem Basha; T. Vengattaraman; P. Dhavachelvan (Journal of King Saud University: Computer and Information Sciences)
Web services are the internet enabled applications for performing business needs, considered as the platform-independent and loosely coupled. Web service compositions build new services by organizing a set of existing services by providing reusability and interoperability. The research problem in web service composition is to obtain best effective services with the composition of services based on maximum quality of services (QoS) and satisfy the user’s requirements. This study reveals various challenges in the QoS parameter for Web service composition because it is difficult to recognize. We have illustrated the related technology by analyzing QoS parameters based on existing algorithms with composition patterns and compared the results.